Insights from the COVID-19 pandemic: trends in development assistance committee countries' aid allocation, 2011-2021 - Shuhei Nomura; Cyrus Ghaznavi; Kazuki Shimizu; Alton Cao; Miho Sassa; Manae Uchibori; Rauniyar Santosh Kumar; Lisa Yamasaki; Hana Tomoi; Haruka Sakamoto (Taylor & Francis Group, 2023)
Background Official Development Assistance (ODA) significantly aids sustainable development in low- and middle-income countries (LMICs). However, the COVID-19 pandemic has impacted aid allocation, posing challenges for attaining the Sustainable Development Goals (SDGs). Objective This study explores and underscores the profound implications of shifts in ODA allocation by Development Assistance Committee (DAC) member countries, resulting from the COVID-19 pandemic, offering a unique perspective on the evolving landscape of international aid. Methods Drawing from the gross ODA disbursement data for LMICs by DAC member countries from 2011 to 2021, a linear regression analysis assessed the changes in ODA amount, ODA-to-gross national income (GNI) ratio, sectoral aid allocation, and the balance between bilateral and multilateral aid, primarily focusing on the differences pre- and post-COVID-19. For non-specialised multilateral agencies' core funding, the OECD's methodology for calculating imputed multilateral ODA was employed to estimate ODA flows. Results The study found an increasing trend in the total ODA provided by DAC member countries from 2011 to 2021. However, the average ODA/GNI ratio showed a slight but significant decrease before the pandemic, followed by an increase after the COVID-19 pandemic. The health sector received the highest percentage of aid after the pandemic, with a marked increase in both bilateral and multilateral aid. However, other sectors such as humanitarian aid, water and sanitation, and energy experienced a significant decrease in sectoral aid share. Conclusions Emerging from this analysis is a strong recommendation for DAC members to re-evaluate aid objectives and escalate their financial commitments to reinforce SDGs and sustainable development efforts. While the rise in health aid is essential, other sectors also require equal focus to offset the ramifications of the COVID-19 pandemic. Understanding the intricacies of aid allocation can improve aid efficacy, culminating in greater, transformative results for recipient countries.